Redescription of the Afrotropical genus Crassabwa Lugo-Ortiz & McCafferty 1996 (Ephemeroptera: Baetidae: Protopatellata) - Kluge, Nikita J.; Gattolliat, Jean-Luc; Salles, Frederico F. (Zootaxa, 2017)
Larvae, subimagoes, imagoes of both sexes and eggs of Crassabwa flava (Crass 1947) are described based on reared material from South Africa, Zambia and Tanzania. Larvae, subimagoes, imagoes of both sexes and eggs of a new species Crassabwa ludmilae sp. n. are described based on reared material from Zambia, Guinea and Mali. Larvae and details of a male subimago extracted from a mature larva of a new species, Crassabwa ameliae sp. n., are described from Zambia, Guinea and Mali. Diagnosis of the genus Crassabwa Lugo-Ortiz & McCafferty 1996 is corrected. Among species formerly attributed to Crassabwa, the species originally described as Centroptilum loweae Kimmins 1949 is moved to Cheleocloeon Wuillot & Gillies 1993 and synonymized with Ch. excisum (Barnard 1932): Cheleocloeon excisum (Barnard 1932) = Cheleocloeon loweae (Kimmins 1949) comb. n., syn. n. The species formerly attributed to Crassabwa and originally described as Centroptilum badium Kopelke 1979 belongs to a new genus, which will be described in a separate paper by N. Kluge. Crassabwa is closely related to Susua Lugo-Ortiz & McCafferty 1998; the species originally described as Cheleocloeon sigiense Gillies 2001 is treated here as Susua sigiense comb. n.; redescription of Susua and argumentation of this new combination will be given in a separate paper.